Pattern of oral diseases and associated contributing factors in pregnant women attending a maternity center in Dhaka city, Bangladesh (Journal of Preventive and Social Medicine, 2021)
Background: Oral health care in pregnancy is often neglected by women and is also not appropriately addressed by prenatal and other health care providers and justify appropriate attention. The purpose of this cross sectional study was to describe percentage of oral disease occurrence and underlying causes in this sample of pregnant women.Methods: The study included 147 women aged between 15 to 49 years receiving prenatal care at the outdoor department of Azimpur Maternal and Child Health Training Institute in Dhaka, Bangladesh were invited to participate in this study from January 2013 to April 2013. Semi-structured interviews were conducted for data collection. Clinical exam data were recorded using validated scales in a special form.Results: Majority (72%) of the women were  between  20 to 24 years.  57%  had secondary  school  education.  88% of the women were unemployed and 52% women had very low family income of BOT s;10000. More than 90% of the women had good oral hygiene practices. However, 68% liked to  have  sugary  snacks  or  drinks  in  between  main meals, 7% visited their dentists during pregnancy , only 3% received advice  for  routine  oral  health  screening  from their prenatal care providers and only 4% women started their antenatal check-up during first trimester.  All  these negative influences might expose expecting mothers to high level of dental caries (54%), dental  erosion  (52%),  gingivitis (100%) and periodontitis (27%). This study also showed that majority of the women acquired oral health information through watching television (61%) or reading  newspaper  (12%)  while  only  4%  received  information from doctors/dent ists throughout their lifetime.Conclusion: The undertaken research highlighted the importance of using media in modifying Bangladeshi pregnant woman's behaviours toward oral health. It also emphasizes the need for inclusion of oral health preventive programme as part of pre and postnatal care. Further study in this area on a large scale will facilitate formulation of appropriate oral health policy to achieve satisfactory oral and general health outcomes during pregnancy and ensure optimum oral health conditions of their offspring.JOPSOM 2020; 39(1): 50-59